The Relationship between Digital Leadership, Job Satisfaction and Job Burnout of Generation x and y during Pandemic COVID-19, Thailand - Jinarat, Veerasak (Journal for Developing the Social and Community, 2022)
The objectives of this research is to study the relationship between digital leadership, job satisfaction and its’ influencing to job burnout. A questionnaire was designed for collecting 442 respondents of working groups in terms of generation X (27 – 41 year of age) and generation Y (42-57 year of age), who located at Ubon Ratchathani, Yasotorn and Amnatcharoen provinces. The statistical analysis are coefficient correlation and multi variate regression analysis. The research results found that digital leadership related no significantly in the same direction to job satisfaction at minimum level, r = .01. Job satisfaction could predicted significantly to job burnout of generation X and Y, with standard error at .06. This can be concluded that there are moderated factors which impact on job burnout of generation X and Y.